Analysis of the Effectiveness, Efficiency and Contribution of Regional Taxes to Regional Original Income in Sub-Regional Provincies Riau Period 2019-2023 - Jhon Raphael Saragih; Yusnaini Yusnaini; Charlene Charlene (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The aim of this research is to analyze the level of effectiveness, efficiency and contribution of regional taxes to Original Regional Income in the sub-region of Riau province for the 2019-2023 period. The data collection technique used is secondary data in the form of financial reports for the 2019-2023 period at the financial djpk. The sample in this study was taken from financial reports registered on the website https://djpk.kemenkeu.go.id/portal/data/apbd. So the data obtained was 12 sub-regions x 5 years = 120 data. The data will be analyzed using quantitative methods. The research results show that the level of effectiveness in the sub-region of Riau province is classified as effective with a percentage of 93%. The level of efficiency in the sub-region of Riau province is classified as inefficient with a percentage of 102%. The level of regional tax contribution in the sub-region of Riau province is quite good with a percentage of 43%.